Programming a contactless smart card system for time monitoring purposes - Capulong, Gayle Russel V. (Animo Repository, 2001)
This report discusses the practicum project which was done in Micrologic Systems Incorporated. It deals with the application of the contactless Smart card for time monitoring. It also gives a background on Smart card technology, how it functions, and the different applications where it can be used. It also discusses the various problems and the solutions in dealing with the projects that utilize the programming of the Smart card system.